Inter-repetition Rest Impact on Percentage of Repetition Completed at Certain Velocity Loss - Martínez-Rubio, Carlos; Quidel-Catrilelbún, Mauricio Elías Leandro; Baena-Raya, Andrés; Rodríguez-Pérez, Manuel Antonio; Pérez-Castilla, Alejandro (International journal of sports medicine, 2024)
This study examined the impact of different inter-repetition rest (IRR) configurations (zero seconds [IRR0], three seconds [IRR3], and self-selected less than five seconds [SSIRR]) on estimating the number of repetitions (Nrep) and the percentage of completed repetitions relative to the maximum number of repetitions possible to failure (%rep) after reaching 10%, 20%, and 30% velocity loss thresholds (VLT). Eighteen men completed three sessions, each with a different IRR configuration, separated by 48-72 hours. Single sets of repetitions to momentary muscular failure were performed against 65%, 75%, and 85% of the one-repetition maximum during free-weight back squat and bench press exercises. No significant differences were reported between IRR configurations for the Nrep ( ≥0.089) and %rep ( ≥0.061), except for %rep after reaching the 20-30%VLT against 65%1RM and the 10-20%VLT against 75%1RM in the bench press exercise ( ≤0.048). Additionally, both Nrep and %rep exhibited high interindividual variability (between-subject CV=14-79%) across the different IRR configurations. The individual %rep-%VLT relationships were slightly stronger than the general %rep-%VLT relationships (median =0.914-0.971 vs. 0.698-0.900). Overall, regardless of the IRR configuration, this novel velocity-based approach does not guarantee the same effort levels across subjects in the free-weight back squat and bench press sets.